2012
DOI: 10.1161/circulationaha.112.110981
|View full text |Cite
|
Sign up to set email alerts
|

Timing, Predictive Factors, and Prognostic Value of Cerebrovascular Events in a Large Cohort of Patients Undergoing Transcatheter Aortic Valve Implantation

Abstract: Background-The objective of this study was to evaluate the timing, predictive factors, and prognostic value of cerebrovascular events (CVEs) after transcatheter aortic valve implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
258
5
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 381 publications
(278 citation statements)
references
References 41 publications
13
258
5
2
Order By: Relevance
“…The association between postdilatation of the aortic valve prosthesis might be due to an increased interaction between the stent frame of the valve prosthesis and the native aortic valve, which might indeed favor the dislodgment of calcific particles from the native valve. One previous study by Nombela-Franco et al [19] reported that further stretching of the calcified native valve during balloon post-dilatation is independently associated with a twofold risk of cerebrovascular events immediately or within the first few hours after the procedure. With regard to procedural risk factors, two previous studies [20] showed that high-intensity transient signals (HITS) observed with TCD occurred during all procedural intervals in TAVR, however, the embolic events appeared to peak during prosthesis deployment.…”
Section: Discussionmentioning
confidence: 98%
“…The association between postdilatation of the aortic valve prosthesis might be due to an increased interaction between the stent frame of the valve prosthesis and the native aortic valve, which might indeed favor the dislodgment of calcific particles from the native valve. One previous study by Nombela-Franco et al [19] reported that further stretching of the calcified native valve during balloon post-dilatation is independently associated with a twofold risk of cerebrovascular events immediately or within the first few hours after the procedure. With regard to procedural risk factors, two previous studies [20] showed that high-intensity transient signals (HITS) observed with TCD occurred during all procedural intervals in TAVR, however, the embolic events appeared to peak during prosthesis deployment.…”
Section: Discussionmentioning
confidence: 98%
“…Preexisting AF and new-onset AF have been associated with an increased risk of stroke after TAVR, 36,37 and the occurrence of previously unknown paroxysmal AF/AT may also be associated with an increased rate of 30-day stroke if anticoagulation therapy is not prescribed early. In fact, the occurrence of AF/AT during 24-hour ECG recording was associated with an 18-fold increase in the rate of cerebrovascular events compared with patients with no AF/AT and an almost 2-fold increase compared with patients with previously known AF/AT.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies identified balloon post-dilatation and valve dislodgement as acute stroke predictors, while new onset atrial fibrillation (AF) was identified as subacute stroke predictor and age, chronic AF, history of stroke, TIA and peripheral vascular disease or coronary artery disease as late stroke predictors (27)(28)(29)(30). The recently presented Sentinel Trial proved that MRI baseline FLAIR Volumes is a strong predictor of a new lesion volume after TAVR (31).…”
Section: Strokementioning
confidence: 99%